Prediction of HIF-1α expression in endometrial carcinoma by enhanced T2∗ weighted angiography and dynamic contrast-enhanced magnetic resonance imaging - Zongyuan Xie; Zongyuan Xie; Liangjie Lin; Changjun Ma; Ailian Liu (Frontiers in Oncology)
PurposeTo explore the value of quantitative imaging parameters by enhanced T2* weighted angiography (ESWAN) and dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) for evaluating the expression of Hypoxia-inducible factor-1α (HIF-1α) in endometrial carcinoma (EC).MethodsData from 122 patients with EC confirmed by clinical pathology were retrospectively analyzed. According to the number of positive cells stained with HIF-1α by immunohistochemistry, patients were divided into two groups: 65 cases with high expression of HIF-1α and 57 cases with low expression of HIF-1α. Clinical data included age, FIGO stage, menopausal status, abnormal uterine bleeding, and pathological type. All patients underwent preoperative 1.5T MRI scans, including ESWAN and DCE-MRI. The amplitude, phase, and R2* values derived from ESWAN and the volume transfer constant (Ktrans), rate constant (Kep), and extravascular volume fraction (Ve) values derived from DCE-MRI were measured by two observers, respectively. The intra-class correlation coefficient (ICC) was used to assess the measurement of reproducibility across observers, and the differences in imaging parameters between the two groups were compared using the independent sample t-test or Mann-Whitney U-test. Binary logistic regression analysis was used to find independent risk factors for HIF-1α expression. The efficacy of selected imaging parameters for predicting HIF-1α expression was assessed using receiver operating characteristic (ROC) curves, and the Delong test was used to compare the area under ROC curves (AUC).ResultsThe consistency between the two observers was good (ICC>0.75). The R2*, Ktrans, and Kep values of the HIF-1α high expression group were higher than those of the HIF-1α low expression group (14.59 ± 4.06 vs. 11.99 ± 2.84 Hz, 0.45 ± 0.18 vs. 0.36 ± 0.14/min, and 2.17 ± 1.10 vs. 1.54 ± 0.80/min) (P< 0.001, P = 0.011, and P =0.001). Binary logistic regression analysis revealed that R2* and Kep values were independent risk factors for HIF-1α expression. The AUC values of R2*, Kep, and their combination for prediction of HIF-1α expression were 0.697, 0.677, and 0.781, respectively. The diagnostic efficacy was significantly improved with combination of R2* and Kep.ConclusionsQuantitative parameters by ESWAN and DCE-MRI showed significant differences between EC patients with low and high expression of HIF-1α, and the combination of ESWAN and DCE-MRI improves the efficacy in prediction of HIF-1α expression in EC, which has an excellent clinical application prospect.